Successful osimertinib treatment for leptomeningeal carcinomatosis from lung adenocarcinoma with the T790M mutation of EGFR - Sakai, Hitomi (ESMO Open, 2017)
Osimertinib is a third-generation tyrosine kinase inhibitor (TKI) of the epidermal growth factor receptor (EGFR) that has been approved for the treatment of metastatic non-small cell lung cancer (NSCLC) positive for the secondary T790M mutation of EGFR. In a preclinical study, it also showed efficacy against leptomeningeal carcinomatosis (LMC) derived from NSCLC resistant to first-generation and second-generation EGFR-TKIs. We now report the case of a patient aged 70 years with symptomatic LMC derived from NSCLC with the T790M mutation of EGFR who showed a clinical and radiographic response to osimertinib.